2005
DOI: 10.1021/cc050038d
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Synthesis and Rapid Photochemical Screening of Organosoluble RuII Photosensitizers

Abstract: Ru(II) complexes of heteroaromatic ligands are photosensitizers of interest in such applications as photovoltaic cells. Their bulk preparation is tedious, time-consuming, and expensive. Their assessments, by measurement of the individual excited-state lifetimes, is incomplete and requires specialized equipment and expertise, as well as time. The identification of new, promising photosensitizers would, therefore, greatly benefit from any time- and cost-saving protocol, if absolute purity is not required for ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In comparison to organic compounds, methods to synthesize libraries of inorganic compounds are grossly underdeveloped. Most attention has focused on the discovery of metal-based catalysts for organic reactions, selective metal-binding agents, and new photosensitizers . Peptide- and oligonucleotide conjugates of metal complexes have been synthesized by solid phase for biological applications, and these compounds have enjoyed great success as biologically active agents and tool compounds. However, their synthesis often involves late-stage attachment of the complex (or ligand) to the biomolecule, where the coordination environment of the complex is preset.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to organic compounds, methods to synthesize libraries of inorganic compounds are grossly underdeveloped. Most attention has focused on the discovery of metal-based catalysts for organic reactions, selective metal-binding agents, and new photosensitizers . Peptide- and oligonucleotide conjugates of metal complexes have been synthesized by solid phase for biological applications, and these compounds have enjoyed great success as biologically active agents and tool compounds. However, their synthesis often involves late-stage attachment of the complex (or ligand) to the biomolecule, where the coordination environment of the complex is preset.…”
Section: Discussionmentioning
confidence: 99%
“…Samples of all four new complexes were submitted to the assessment protocol [23] that we have used several times to gauge photosensitizer ability [9,12,14,24,25] 2+ and TEOA, were all required to produce the precipitation. We also found that no precipitation occurred in the dark; light -even sunlight through a window -was required.…”
Section: Photosensitizationmentioning
confidence: 99%